A community typology of social change devised from the bottom-up - Badstue, Lone B. (International Maize and Wheat Improvement Center, 2019)
Presented by Lone Badstue (International Maize and Wheat Improvement Center), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.